The Philosophical Dilemma of the Implementation of Justice Theory: Problems in Utilizing Land Rights between the Amungme Indigenous Tribe and PT Freeport Indonesia - Pratama, Muhammad Bintang; Afiq, Muhammad Adib; Cindi F, Novita Ratna; Auril, Savira (UIR Press, 2020)
This study analyzes the philosophical dilemma of the implementation of the theory of justice, the problem of the use of land rights between the Amungme Indigenous Tribe and PT Freeport Indonesia. This research is normative legal research using secondary data sources through prescriptive literature studies. The results show that there are problems in the use of land ownership rights; there are contradictions in the use of reasons for claiming ownership rights over the disputed land. The Amungme Adat tribe adheres to the theory of natural law with concrete implementation in the form of traditional customs which considers disputed land as ancestral heritage land, which is the absolute right of the Amungme Adat tribe. Meanwhile, PT Freeport Indonesia uses positivist legal theory with concrete implementation in the form of the use of Contract of Work and Agreement as positive law which is used as a strong basis for claiming ownership rights over the disputed land. In this research, we will discuss the philosophical dilemma of the implementation of the theory of justice comprehensively, the problem of the use of land rights between the Amungme Indigenous Tribe and PT Freeport Indonesia based on the use of the theory of justice. The limitation of this research lies in the study using literature data sources without empirical research. In the future, it is hoped that similar research can use this research as an essential reference in conducting research that can obtain factual data in the field so that it can provide more accurate results.